The Efforts to Improve Teacher Performance Through School Principal Leadership, Job Satisfaction and Work Motivation - Susilo Surahman; Eva Desriyantika; Endang Damaris Koli; Akhmad Ramli; Hasmirati Hasmirati (Departement of Mathematics Education, 2023)
The goal of this research is to explain the impact of leadership style, motivation, and job satisfaction on teacher accomplisment at a single Islamic private boarding school in West Java. The nature of this study is quantitative.This study's participants were all teachers. For 41 respondents, data was collected using saturated samples. This study used a questionnaire and paperwork to gather data, and multiple regression analysis was done using SPSS 22 software. According to the study's findings, leadership style, motivation, and work happiness were all connected to the instructors associated with the F significant results. 0.05) and an R-squared = 0.664. Leadership style, motivation, and work satisfaction were all approved by 66.4% of respondents. Leadership style, motivation, and work satisfaction were all approved by 66.4% of respondents. The other factors are handled by variables outside of the scope of this research.